2020
DOI: 10.34172/jcvtr.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral nicorandil pre-treatment on ST resolution and clinical outcome of patients with acute ST-segment elevation myocardial infarction undergoing primary coronary angioplasty: A randomized placebo controlled trial

Abstract: Introduction : Literature has shown the effects of intravenous/intracoronary nicorandil on increased myocardial salvage in patients with ST-segment elevation myocardial infarction (STEMI) treated with mechanical reperfusion. However, the possible cardioprotective effect of oral nicorandil on the clinical outcome prior to primary coronary angioplasty is not well documented. Our aim was to assess the effect of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several promising investigations are currently being conducted to prove the reliability of nicorandil use during mechanical reperfusion after the ACS. (14). Therefore, the purpose of our comprehensive meta-analysis is to investigate whether this may help protect the heart from injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Several promising investigations are currently being conducted to prove the reliability of nicorandil use during mechanical reperfusion after the ACS. (14). Therefore, the purpose of our comprehensive meta-analysis is to investigate whether this may help protect the heart from injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized placebo-controlled trial including 240 patients with STEMI and PCI, it was demonstrated that pretreatment with nicorandil prior to PCI reduced the incidence of MACE by 50%. MACE included death, ventricular arrhythmia, heart failure, and stroke [175]. It was reported that nicorandil reduced the incidence of MACE in patients with AMI and PCI [165,176].…”
Section: The Use Of Nicorandil In Treatment Of Patients With Ami or C...mentioning
confidence: 99%
“…Oral nicorandil before emergency PCI can achieve similar effects to intravenous or intracoronary use. [60] A randomized controlled study showed that compared with the control group, patients with STEMI who received oral nicorandil tablets for half a year after surgery had a smaller myocardial infarction size, [61] and it is recommended to continue taking nicorandil after PCI. Small sample studies have shown that the traditional Chinese medicine Tongxinluo can improve cardiac microcirculation by protecting endothelial barrier function and can reduce the occurrence of no-reflow and infarct size in patients with STEMI.…”
Section: Prevention and Treatment Strategies For Cmd During The Emerg...mentioning
confidence: 99%